2006
DOI: 10.1109/tpel.2005.861113
|View full text |Cite
|
Sign up to set email alerts
|

Converter circuit design, semiconductor device selection and analysis of parasitics for micropower electrostatic Generators

Abstract: Abstract-For various medical monitoring and sensing applications it is desirable to power the electronics by scavenging energy from any locally available source. An electrostatic motion-driven generator for low-frequency (human body) motion has been developed by the authors using microelecromechanical system technology. The prototype generates pulses of 250 V on a 10-pF capacitor. This paper examines the design of a circuit and semiconductor devices to convert this energy to a low voltage. Because of the very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…In an analysis of power processing circuits for the CFPG, it was shown that the power converter attached to this device needs to have an off-state impedance of more than 10 12 and less than 1 pF of input capacitance to maintain 80% of the generated energy [173]. To achieve this high level of impedance, a thin-layer silicon-oninsulator MOSFET was designed.…”
Section: Power Electronics For Micropower Generatorsmentioning
confidence: 99%
“…In an analysis of power processing circuits for the CFPG, it was shown that the power converter attached to this device needs to have an off-state impedance of more than 10 12 and less than 1 pF of input capacitance to maintain 80% of the generated energy [173]. To achieve this high level of impedance, a thin-layer silicon-oninsulator MOSFET was designed.…”
Section: Power Electronics For Micropower Generatorsmentioning
confidence: 99%
“…A number of architectures of conditioning circuits exist [15]. Virtually in all of them, the transducer conditioning is adjusted by a control signal derived from the parameters of available external vibrations (that can, in the general case, vary).…”
Section: A Architecture Of a Vehmentioning
confidence: 99%
“…Unfortunately a 10 H inductor is difficult to integrate due to its physical size and due to constraints that must be placed on its parasitic capacitance [9]. It is preferable to use a lower inductor value.…”
Section: Requirements Relating To System Integrationmentioning
confidence: 99%